SISTEM PENJUALAN MENGGUNAKAN WEB SERVICE PADA PT. GLOBAL ELEKTRONIK SEMARANG (Information Technology and Telematics, 2014)
Abstract : PT.  Global electronics is one type of profit-orientedenterprises, the main products of electronic equipment. The company has three branches in the city of Semarang. Web services technology is one technology that can be used on a network-based system for building a distributed application. By using web service then there are two applications on a system built, the application on the server and on the clientapplication.  With the internet web site development is the management can arrange promotion up to date in accordance with the type and brand of electronics as well asthe market price and can match the needs of consumers. The purpose of this thesis is to build a web serviceapplication system electronic sales at PT. Global ElectronicSemarang in order to facilitate the exchange of data andinformation to consumers. With adannya electronic sales website, consumers can findthe latest product information and can make reservations online consumers that can be accessed from any location. With the web service allows the product to be sold in twowebsites,  one of which is owned by PT.  Global ElectronicSemarang and the other belonging to other parties working together.Keywords: Web Sales, Web Service, Global Electronic